2012
DOI: 10.1105/tpc.112.097618
|View full text |Cite
|
Sign up to set email alerts
|

required to maintain repression2 Is a Novel Protein That Facilitates Locus-Specific Paramutation in Maize

Abstract: Meiotically heritable epigenetic changes in gene regulation known as paramutations are facilitated by poorly understood trans-homolog interactions. Mutations affecting paramutations in maize (Zea mays) identify components required for the accumulation of 24-nucleotide RNAs. Some of these components have Arabidopsis thaliana orthologs that are part of an RNA-directed DNA methylation (RdDM) pathway. It remains unclear if small RNAs actually mediate paramutations and whether the maize-specific molecules identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 73 publications
1
57
0
Order By: Relevance
“…The association of plant paramutation with DNA-methylation has been established in multiple plant paramutation systems [12,[15][16][17][18][19][20][21]. Bearing in mind these results we carried out a comparative analysis of the genome-wide 5-cytosine methylation and a random identification of specific differentially methylated sequences in cv.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association of plant paramutation with DNA-methylation has been established in multiple plant paramutation systems [12,[15][16][17][18][19][20][21]. Bearing in mind these results we carried out a comparative analysis of the genome-wide 5-cytosine methylation and a random identification of specific differentially methylated sequences in cv.…”
Section: Discussionmentioning
confidence: 99%
“…Among the above mentioned maize loci, the most significant progresses have been achieved in the study of b1 and pl1 and the identified genes required for paramutation at these two loci: mediator of paramutation (mop1 [9] and mop2 [10]) and required to maintain repression (rmr1 [11], rmr2 [12], rmr6 [13], and rmr7 [14]) were found to encode proteins involved in small interfering RNA (siRNA) biogenesis and RNA directed DNA methylation (RdDM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic screens have successfully identified mutants that are defective in the establishment and/ or maintenance of paramutation (Dorweiler et al, 2000;Hollick and Chandler, 2001). The molecular characterization of these mutants has revealed that most affect components of the RdDM pathway (Alleman et al, 2006;Erhard et al, 2009;Sidorenko et al, 2009;Sloan et al, 2014), while others are novel proteins (Barbour et al, 2012). In some cases, these mutants have been shown to have locus-specific effects on DNA methylation (Lisch et al, 2002;McGinnis et al, 2006;Sloan et al, 2014), but the genome-wide effect of these mutations on DNA methylation has not been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The developmental defects observed in rpd1 mutants are both distinct and nonheritable (Parkinson et al 2007) and therefore unlikely to be related to TE-derived mutations. These defects also appear unrelated to siRNA-induced silencing because other maize mutants affecting siRNA biogenesis, including rpd/e2a, are developmentally normal (Hale et al 2007;Stonaker et al 2009;Barbour et al 2012). We hypothesize that maize has co-opted RPD1/Pol IV to transcriptionally control specific alleles of genes for which TEs and TE-like repeats act as regulatory elements.…”
mentioning
confidence: 99%